Liposuction and Brazilian Butt Lift (BBL): New trends in body augmentation and implications for courtship behavior in Nigeria - Emmanuel Nwakanma (SIMULACRA: JURNAL SOSIOLOGI, 2022)
Liposuction and Brazilian Butt Lift have been identified as the most common cosmetic surgeries performed worldwide. In Nigeria, the appeal and demand for liposuction and gluteal augmentation (Brazilian Butt Lift) has increased with many women opting for it and highlighting its benefits in the media. This study investigates this new trend and its implications for courtship behavior. The study adopts the Self-discrepancy Theory and the Theory of Value as theoretical framework which in adjunct explains the issues associated with body modifications and its implications for courtship behavior. The cross-sectional survey design was adopted, and data were collected using questionnaires, in-depth interviews, and peer-reviewed journals. The study was conducted in four States in Nigeria. The sample size for the study is 410. Data were analyzed using descriptive statistics and thematic analysis. The result of this study has shown that whereas women have different psychosocial reasons for opting for cosmetic surgery, this new trend unintendedly impacts the perception of men about women and courtship behavior. The study recommends regular public health education on the ramifications of cosmetic surgeries. Also, there is the need to introduce psychological screening in the procedures for cosmetic surgeries which helps to influence the choices of women on cosmetic surgery.